(untitled) (Research, Society and Development, 2021)
The present work aims to evaluate the influence of substrate and fertilization on the development and quality of seedlings of garden joy (Salvia splendens Ker Gawl.). A completely randomized design was adopted, with four treatments consisting of different fertilization methods: T1 - control; T2 - fertilization by fertigation; T3 - foliar fertilization and T4 - fertilization by fertigation + foliar, with five replications, each experimental unit being composed of four seedlings. The seedlings were transplanted in trays of 15 wells with peat substrate, fertilization was carried out in three stages weekly from the transplant. Plant height, stem thickness, number of leaves, length and root green mass and clod cohesion were evaluated using scales from 1 to 5. It was observed that the plant height was higher in the T4 treatment, however, in this treatment the plants were isolated. The evaluated characteristics of the roots had better performance in the TI and T2 treatments, as well as better clod cohesion; seedlings with the addition of fertilization by fertigation show greater tray uniformity in both size. In this way, fertilization by fertigation is recommended for the production of seedlings of garden joy.